Synthesis of Nanocomposite: I-Naphthaleneacetate-Zinc-Aluminium-Layered Double Hydroxide - Wong, Dickens Vui Foo (2002)
Formation of organic-inorganic nanohybrid material of 1-naphthaleneacetate in the lamella of Zn-Al-Iayered double hydroxide (ZANOL) with and without microwave-assisted aging was done and the properties of the resulting materials were compared. For both methods, the results showed that the intercalation of 1- naphthaleneacetate (NAA) anion into the Zn-Al-Layered double hydroxide lamella are readily accomplished, resulting in a Zn-AI-NAA nanocomposite (ZAN AN), with the expansion of the interlayer spacing from 9.0 A. in the layered double hydroxide to 20.0 A. in the nanohybrid. This expansion is to accommodate the NAA anion of larger size than nitrate. The resulting materials afforded well ordered organic-inorganic nanolayered structure. Further characterization of the resulting materials including the true density, organic-inorganic content, surface area and morphology, was also carried out. Both ZANOL and ZANAN exhibited good neutralizing and, buffering power toward RN03 and NaOH solutions. Deintercalation of the NAA ions from the interlayer of ZANAN could be done in an excessive volume of HN03 or NaOH solutions. NAA ions could be adsorbed on ZANOL if added into an aqueous solution of NAA. At the same time, the NAA ions adsorbed by ZANOL, could also be desorbed into the aqueous solution. The process of adsorption-desorption is a continuous process and no equilibrium was achieved, even up to 14 days. Both ZANAN and ZANOL used in the tissue culture study of oil p alm clones of E7, E8, L272, L273 and L255 did not assist in the initiation of roots. Instead, the results showed that the MS medium with the presence of NAA ions inhibited the growth of roots.